Correlation between leukocyte count and hemoglobin with the incidence of febrile seizures at RSUD Abdul Wahab Sjahranie Samarinda - Muhammad Harbiyan Acikdin; Annisa Muhyi; Vera Madonna Lumban Toruan (Pediatric Sciences Journal, 2022)
Background: Febrile seizures occur at the age of 6 months to 5 years, ranging from 2-5% of cases in children. The sign when the body is fighting infection is the process that occurs, the presence of infection in the body causes a change in the leukocyte count, and high fever can trigger a decrease in hemoglobin. This study aims to determine the relationship between leukocytes and hemoglobin with the incidence of febrile seizures in children. Methods: This research is analytic observational with a cross-sectional design. The research data was taken from medical records at Abdul Wahab Sjahranie Hospital Samarinda with a purposive sampling method. The study sample was children aged 6 months to 5 years who had febrile seizures and fever without seizures and met the inclusion and exclusion criteria. Statistical analysis of this study used the chi-square test. Results: The chi-square test results were obtained on hemoglobin and leukocyte count with the incidence of febrile seizures with a p-value on the number of leukocytes (p=0.032) and hemoglobin (p=0.019). Conclusion: There is a significant relationship between the number of leukocytes and hemoglobin with the incidence of febrile seizures in children.